Wintrobe's clinical hematology - Greer, John P. (Philadelphia : Wolters Kluwer Lippincott Williams & Wilkins Health, 2014)
With the 13th edition of Wintrobe's Clinical Hematology, Dr. Greer brings forth another text that bridges the gap between the clinical practice of hematology and the basic foundations of science. Revised to include a greater emphasis placed on biology and pathophysiology, this book offers the reader a clear understanding of the relationship between basic molecular biology and every aspect of the clinical practice of hematology. Coupled with this comprehensive overview, Dr. Greer presents a clear focus on clinical diagnosis and treatment of disease. Dr. Greer has added 7 entirely new chapters that are concisely reduced and dived in order to present more focused material. Additionally, the text provides a special section dedicated to transplantation, international editors, and over 1,400 full-color illustrations. This latest edition is an excellent resource for anyone studying Hemotology, Oncology, Internal Medicine, or Pathology. Features: 30% of the chapters have additional or new contributors, greater emphasis on molecular genetics and pathophysiology, increased number of hematopathology illustrations, diagrams, figures, standard and electron micrographs, algorithms, schemas, and protocols--all in color, 4-color halftones and 2-color computer generated illustrations spread throughout the book to reinforce understanding and application of method. The last three new chapters are entirely dedicated to Transplantation--Provided by publisher.
Includes bibliographical references and index.
Keywords: Blood; Hematologic Diseases; Hematology